Design and Development of a MOOC for Academic Institution in Iraq - Inas Ismail Imran; Amer S. Elameer; Rafah Al-Hamdani (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Massive Open Online Courses, shortly MOOCs, are a phenomenon in online education nowadays because it supports teaching and learning processes in academic institutions. Therefore In this paper a new design of MOOC website have been developed for Iraqi academic institution; specifically for Informatics Institute of Higher Studies. The new website is designed and implemented as an interactive educational platform using PHP7 scripting language (back end code that control front end logic), MySQL to build the database, HTML language used to design the layout of website, CSS language is used to add style to the web page finally JavaScript programming language is also used to add dynamic elements and action to the web page. The result of the project is to establish MOOC website based on the general curriculum provided by the Iraqi ministry of higher education to spread usage of E-learning in Iraq and also establish the first E-Iraqi University.